BIOEFFICACY OF NEWER INSECTICIDES AGAINST TOMATO FRUIT BORER, HELICOVERPA ARMIGERA (HUBNER) ON TOMATO, LYCOPERSICON ESCULENTUM MILL UNDER FIELD CONDITIONS - L. K. MEENA; S. V. S. RAJU (The Bioscan, 2014)
For tomato fruit borer management six newer insecticides insecticides were taken viz., spinosad 45% SC, fipronil 5% SC, profenofos 5 % EC, indoxacarb 14.5% SC, NSKE 5% w/w and NPV. The total two numbers of sprays were done. The descending order of efficacy was as Spinosad 45% SC (45.44) > fipronil l5% SC (43.07) > Profenofos 50% EC (31.51) > indoxacarb 14.5% SC (29.56) > NSKE 5% w/w (28.59) > NPV (25.82). All the treatment differs significantly with each other except 1DAT, NSKE (20.08) and NPV (20.02), 5 DAT, Indoxacarb (34.02) and NSKE (33.41) and again, 10 DAT Indoxacarb (33.14) and NSKE (32.28) of 2nd spray were found at par with each others. In this experiment Spinosad was found most effective insecticides and fipronil, profenofos and indoxacarb was also found effective for fruit borer management.